Household demand for consumer goods in developing countries : a comparative perspective with developed countries - Selvanathan, Eliyathamby A.; Selvanathan, Saroja; Jayasinghe, Maneka (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book analyses the household demand for consumer goods using a diverse database, consisting of 45 developed and developing countries. Household consumption patterns have undergone dramatic changes due to rapid economic growth, increasing household income and changing demographics. Using the most recent data available and the latest econometric techniques, the authors model demand for 12 different commodities such as food, alcohol and tobacco, housing, health, transport, health communication, and recreation and provide insightful comparisons of consumption patterns in developed and developing countries. The analysis presented in this book highlights valuable policy insights for planning government budgetary allocations and implementing policies towards an enhanced standard of living for people. The book also provides some important guidance for researchers interested in the theory and empirical application of the analysis of consumer demand"--
Keywords: Consumers -- Developing countries; Consumption (Economics) -- Developing countries; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Economics / Microeconomics; BUSINESS & ECONOMICS / Consumer Behavior